(3GdbQGQGJ GdSHYI GdPcjI dEOGQI GdejRGfjI GdefRdjIs - (3Cdajf, eGQj cdjQs; (3GdYGeQj, NGdOs; (3dGQSjf, cQjSJjfs ((3GdbGgQIs (3OGQ GdaGQhbs, 2008)
(3jYQV GdcJGH WQjbI LOjOI ddRhLjf defGbTI TFhfgeG GdeGdjI eYG, ef NdGd GdGSJYGfI HGdCSGdjH h GdbhGYO GdeJHYI ai GdeDSSGJ GdJLGQjIs
(3GdeMJhjGJ (B: (3JCSjS GdTQcI GdCSQjI (B-- (3HOA fTGW GdTQcI GdCSQjI (B-- (3MSGH GdJOabGJ GdfbOjI (B-- (3JMOjO GdbjeI GdUGajI dQCS GdeGd (B-- (3EOGQI GdSjfGQjhgGJ GdeSJbHdjI GdeJhbYI (B-- (3GdbQGQGJ GdSHYI GdPcjIs
4 12 13 20
Keywords: (3GdEOGQI GdefRdjIs; (3GdGbJUGO GdefRdjs